Report of the Working Group on Health Systems Research and Biomedical Research and Development the Tenth Five Year Plan - Planning Commission (Planning Commission, 2001)
Prof. V. Ramalingaswamy - the Bhishm Pittamah of health and biomedical research in India - was named the Chairman of this Working Group. We had hoped that this Report would go under his signature. But that was not to be. After a period of ill health, he passed away on 28 May, 2001. In his long and illustrious career as an educationist, research scientist and institution builder, Dr. Ramalingaswamy played a pivotal role in the evolution of several national health and nutrition programmes. During the last few months, in spite of his ill health he continued to devote time and attention to inspire and guide the Members of the Working Group in laying the foundations for an excellent report in this critical area of the 10th Plan.
Government of India, Planning Commission